Journey of Patients With Cancer: A Systematic Evaluation at Tertiary Care Center in India. (June 2014) - Bhatnagar, Sushma; Goyal, Alka; Sharma, Anchal; Joshi, Saurabh; Ahmed, Sayed Mehmood
In cancer patients early institution of therapy placed a very important role and delay in the diagnosis and treatment can cause catastrophe. Affirm step to cut shot this delay requires detailed information about each step of patient referral journey and for fulfillment of above aim, we interviewed 101 patients, to calculate the elapsed time at each step. Result revealed that onset of symptoms to median time of presentation to general practitioner is 20 (9 - 28) days, time consumed in state based hospital is 100 (15- 167) days while in Delhi based hospital is 56 (18 - 100) days. Higher cure rate (38.2%) in patients presented within 3 months of development of cancer symptoms then those presented late. Study concluded that primary physician and all the referral hospital attributed important role in early diagnosis and treatment of cancer.